Optimasi Pembagian Beban Pada Sektor Pembangkitan Pekanbaru PLTD/G Teluk Lembu Pada BUS 20 KV Dengan Metode Newton - Arbi Wahyu; Firdaus Firdaus; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The electricity demand always increases and electricity consumption too changes every time. The cost of power generation also changes when the electric load changes. planning is required to determine the portion of the generation of each plant in order to obtain an economical generation. In this study, solving solution using Newton's method aided with software Microsoft Office Excel and Matlab 2008b. The results of the testing that has been done, that PLTMG Haleyora operates at 08.00 am at 14.484 MW, while the maximum operating diesel from 10.00 am to 24.00 pm for 7 MW. while the peak load period all plants operate optimallyKeywords: Optimization, Load, Generation, Method Newton